2012
DOI: 10.1016/j.jjcc.2012.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of medium-sized atrial septal defect in pediatric cases

Abstract: Qp/Qs and RVEDV/LVEDV of medium-sized ASD increase together in childhood. Re-evaluation before adulthood should be considered in patients with no indications of ASD closure in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…One simple explanation is that we avoid overlap examinations in our cohort. The other possible explanation could be that the some ASD will naturally close before pre-school, and the number may be overestimated [11]. However, in several studies, the wide ranges (4-70%) of spontaneous closure of ASD were reported [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…One simple explanation is that we avoid overlap examinations in our cohort. The other possible explanation could be that the some ASD will naturally close before pre-school, and the number may be overestimated [11]. However, in several studies, the wide ranges (4-70%) of spontaneous closure of ASD were reported [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing RV to LV size for RV assessment is not an entirely new concept and has been applied for the assessment of RV size in pediatric patients using angiography . In the PAH population, the RV end‐diastolic dimension and RV end‐diastolic area by echocardiography in the four‐chamber view have been compared to LV and used to identify RV dilation using a normal ratio of 0.5–0.7, and 0.8–1.0, 1.1–1.4, and ≥1.5 as cutoffs for mild, moderate, and severe dilation, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…13 Comparing RV to LV size for RV assessment is not an entirely new concept and has been applied for the assessment of RV size in pediatric patients using angiography. [14][15][16] In the PAH population, the RV end-diastolic dimension and RV end-diastolic area by echocardiography in the four-chamber view have been compared to LV and used to identify RV dilation using a normal ratio of 0.5-0.7, and 0.8-1.0, 1.1-1.4, and 1.5 as cutoffs for mild, moderate, and severe dilation, respectively. 17 Furthermore, RV/LV end-systolic diameter measured in the parasternal short-axis view by echocardiography correlates well with invasive hemodynamic measurements in children with PH and an RV/LV ratio >1 was associated with adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Saito et al . [ 6 ] treated an infant with a defect size that enlarged from 9 mm to 27 mm over a period of 9 years. In both cases interventional treatment became unsuitable and finished as surgical closure.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial septal defect occurs at an incidence rate 1 per 1500 live births, and nowadays the preferred method of treatment is transcatheter closure. Many previous reports regarding natural history of small atrial defects have described spontaneous closure [ 1 6 ]. However, large defects usually increase in size with age [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%